Superelastic and robust carbonaceous nanofibrous aerogel with high pressure-sensitivity, excellent thermal insulation and high photothermal-conversion efficiency. (June 2022) - Wan, Fuqiang; Wei, Jingjiang; Zhu, Chenglong; Ping, Hang; Wang, Hao; Wang, Weimin; Fu, Zhengyi
Abstract: Carbonaceous aerogels have attracted extensive research interest due to their impressive physical properties such as high porosity, high electrical conductivity, low thermal conductivity, and low density. However, the low durability of the aerogels under compression is a concern. In this work, superelastic, multimodal porous, chitin-derived carbonaceous nanofibrous aerogel (CAs) whose mechanical properties were tunable were prepared by a facile and cost-efficient carbonization method. The CAs exhibited remarkable elasticity and stability under compression, even under extreme temperatures. After the CAs had been subjected to one loading-and-unloading cycle under the compressive strain ( ɛ ) of 50%, the CAs exhibited a very low energy-loss coefficient (0.15). Moreover, the CAs maintained their structural integrity with little deterioration of mechanical properties after 1000 cycles. The structural stability and the superelasticity of the CAs conferred the materials a fast and accurate piezoresistive response, which renders it promising for the fabrication of pressure sensor with a high gauge factor (GF, 14.24) under low ɛ (up to 2%). Furthermore, the biomass-derived cost-efficient CAs demonstrated high photothermal-conversion efficiency of solar energy (96.4%) and excellent thermal insulation. Therefore, the CAs exhibit potential applications in the fabrication of pressure sensors, the production of thermal-insulation materials, and the desalination of seawater. Graphical Abstract: ga1 Highlights: A chitin-derived carbonaceous nanofibrous aerogel (CAs) is prepared. The CAs exhibits super-elasticity and superior fatigue resistance. The mechanical properties are easily tunable by varying fabrication conditions. The CAs is versatile: piezoresistive, photothermal conversion and heat insulation.